Harmonizing Global Digital Trade: Integrating Tax Governance and Consumer Protection Regulatory Frameworks - Dipangshu Dev Chowdhury; Nabaraj Bhowmik (Yayasan Cerdas Pedia Indonesia, 2026)
Digital trade transformation creates deep structural dissonance within international law, clashing outdated normative systems against modern commercial realities. This study employs doctrinal legal research to examine the erosion of national tax bases and the degradation of consumer protection in cross-border transactions. Findings reveal that conventional taxation theories relying upon permanent establishment have become obsolete, thus facilitating aggressive profit shifting and fiscal injustice against developing nations. Simultaneously, consumers face systemic vulnerabilities due to information asymmetry, algorithmic manipulation, and a vacuum in extraterritorial redress mechanisms. Although multilateral initiatives like the OECD policies aim for regulatory harmonization, global governance remains trapped within continuous multilateral fragmentation. Consequently, this research proposes a reconstructive framework integrating Regulatory Technology, specifically Blockchain and Artificial Intelligence, alongside institutional capacity building and ethical platform governance. This holistic approach is absolutely essential to effectively bridge jurisdictional gaps and ensure an equitable, inclusive, and resilient global digital economy for future generations worldwide.